The inevitable priesthood of peace: bishop Béla Gencsy as part of the peace advocates’ movement - Ibolya Szamborovszky-Nagy; Szamborovszkyné Nagy Ibolya; Самборовскі-Нодь Ібоя (Інститут українознавства ім. І. Крип’якевича НАН України, 2024)
Abstract. The study aims to illustrate through the example of Béla Gencsy, the bishop of the Transcarpathian Reformed Church (TRC), how the Soviet power forced the Protestant church leader into the movement of peace advocates’. Additionally, it seeks to convey how this situation affected the bishopʼs relationship with his congregants and the consequences for both his denomination and his personal life. The research methodology is based on the analysis of little-known and unknown archival sources from the Central State Archives of the Highest Authorities and Administration of Ukraine, the Archives and Museum of the Transcarpathian Reformed Church, as well as contemporary documents and press materials from that time. The scientific novelty of the paper lies in the fact, that the relationship between churches and the peace advocates’ movement is rarely the focus of Ukrainian historiography. This research is particularly relevant, as the Cold War extended beyond political, diplomatic, military, economic, and scientific spheres, interacting significantly with religion – thereby influencing ecclesiastical organizations and their leaders. Therefore, this study specifically focuses on the significant impact of the so-called peace priest movement on the lives and activities of religious leaders, which affected not only individuals but also communities. The study aims to provide a bottom-up perspective on the peace advocates’ movement through the activities of Gencsy Béla, the bishop of TRC. It has been revealed, that when Gencsy assumed leadership of the TRC in the early 1950s, he did not yet grasp the intentions and plans of the Soviet authorities. At that time, he believed that by joining the peace advocates’ movement, he might gain greater personal freedom as well as that of his denomination. However, over time, as dean and later bishop, Gencsyʼs understanding evolved: he recognized that the expectations and pressures from state power increasingly constrained him. The space for religious practice and international relations with denominational partners did not become broader or freer. Consequently, by the early 1970s, Gencsy had already resigned to the Soviet reality: he saw that his room for manoeuvre, despite the peace priest status, could not be described as free of constraints, nor independent or autonomous at all. To a certain extent, his limited room for manoeuvre was also because he did not fully submit to the state ideology, but only adhered to and – with his priests and the Reformed believers – obeyed the Soviet religious laws. From certain point of view, this state of affairs could indeed cover the notion of straddle, which was used to describe Genchy by the Council for the Affairs of Religious Cults official in Transcarpathia in the early 1950s. However, this may also serve as evidence that he was neither a KGB agent nor an embedded informant. At least, no sources have yet emerged to refute this claim.

Резюме. На прикладі єпископа ЗРЦ Б. Ґенчі розкрито, як радянська влада «втиснула» керівника протестантської Церкви в рух прихильників миру. Зроблено спробу простежити, як це вплинуло на стосунки між священником (і єпископом) та його вірянами і які мало наслідки для існування конфесії та особистого життя священнослужителя. Проаналізовано маловідомі й невідомі архівні джерела Архіву та Музею Закарпатського реформатського церковного округу, Центрального державного архіву вищих органів влади та управління України, а також документи й публікації у пресі того часу. Стверджено, що наукова новизна роботи полягає в тому, що зв’язки Церков і руху прихильників миру досить рідко потрапляють у фокус уваги української історіографії, а це дослідження дає можливість заповнити білі плями, оскільки «холодна війна» виявлялася не тільки в політичній, дипломатичній, військовій, економічній та науковій площині, а як на Заході, так і на Сході вступила у визначальну взаємодію з релігією, а отже, із церковними структурами та їхніми керівниками. Саме тому в публікації акцентовано на впливі на життя та діяльність релігійних діячів т. зв. руху миротворчого духівництва, наслідках примусу до участі в ньому не тільки для окремих осіб, а й загалом для спільнот. Через діяльність єпископа ЗРУ Б. Ґенчі зроблено спробу розкрити певні особливості руху прихильників миру, застосувавши підхід «знизу вгору» (bottom-up approach). Виснувано, що коли Б. Ґенчі на початку 1950-х років очолив керівництво ЗРЦ, то ще не усвідомлював намірів та планів радянської влади, а вважав, що якщо доєднається до руху прихильників миру, то, можливо, матиме більший простір для маневру як для себе особисто, так і для конфесії загалом. Проте зауважено, що зі зростанням очікувань, спонукань, тиску органів влади та їхніх керівників, які переходили у примус, для Б. Ґенчі – декана, а згодом єпископа – з часом стало зрозуміло, що це не так, адже практикування релігії не стало ні ширшим, ні вільнішим, не з’явилося і більше можливостей для підтримання транскордонних зв’язків з іншими реформатами. Констатовано, що на початку 1970-х років наміри Б. Ґенчі зламалися об радянську дійсність: він бачив, що його можливості маневрувати – навіть попри участь у русі миротворчого духівництва – не уникли примусу, а тим більше на стали незалежними чи автономними. Обмеження простору його діяльності певною мірою потрактовано як наслідко того, що він не цілком підкорився державній ідеології, а лише дотримувався радянського законодавства у сфері релігії та вимагав цього від свого духовенства і вірних. Такий стан інтерпретовано як двоїстість, у чому Б. Ґенчі на початку 1950-х років звинувачував закарпатський обласний уповноважений Ради у справах релігійних культів. Водночас зауважено, що це може бути і підтвердженням того, що єпископ не був агентом або таємним інформатором КДБ. Принаймні до сьогодні не виявлено архівних матеріалів, які б це спростували.
Неминучість участі в «миротворчому духівництві»: єпископ Бейла Ґенчі в русі прихильників миру
Keywords: Béla Gencsy; Cold War; peace priest; Soviet Union; Transcarpathia Oblast; Transcarpathian Reformed Church; World Council of Churches